Enhancement of boron nitride nanosheet/cellulose nanofiber modified laminated insulating paper - Daning Zhang; Siyu Wang; Xinnan Zhai; Wenrui Tian; Jiongting Jiang; Chao Li; Guan-jun Zhang (AIP Advances)
The extra-high voltage casing faces severe heat dissipation demands during operation, which places higher requirements on the thermal conductivity, mechanical properties, and electrical properties of insulating paper in the oil–paper insulation system. However, enhancing the overall performance of materials by only using a single nanomaterial remains a significant challenge. Consequently, this paper proposes integrating laminate design with nanomaterial doping modification to engineer boron nitride nanosheet/cellulose nanofiber (BNNS/CNF) modified laminated composite insulating paper. The synergistic effect of BNNS and CNF leads to a notable enhancement in the mechanical properties of the insulating paper, with the tensile strength increasing by up to 20.4%. The BNNS, CNF, and cellulose are arranged layer by layer under gravity to form a “brick mud” structure, which synergistically constitutes a thermal conductivity network, and the thermal conductivity is increased by up to 15.82%. In addition, the laminate structure and nanofillers optimize the electric field distribution inside the modified paper, thereby enhancing the DC breakdown field strength by 22.36% and reducing the power frequency dielectric loss by 52.51%. The laminated boron nitride nanosheet/nanocellulose modified insulating paper exhibits excellent overall performance, positioning it as a promising cellulose-based insulating paper material with significant potential.